Цивільно-правові способи захисту спадкових прав - Заіка, Ю.; Zaika, Y. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджуються проблеми захисту прав спадкоємців та обрання найбільш ефективного способу захисту цивільних прав після відкриття спадщини. Таким найефективнішим способом захисту спадкових прав спадкоємцями за законом четвертої та п’ятої черги є визнання права (встановлення факту споріднення, родинних відносин, перебування на утриманні). Способом захисту спадкових прав є і зміна правовідношення, яка може відбуватися шляхом заміни суб’єкта правовідношення при усуненні від спадкування негідних спадкоємців. Аргументовано пропозицію про необхідність віднесення до категорії негідних спадкоємців осіб, які вчинили умисні злочини проти спадкодавця In the article the author researches the problems of protection of the rights of heirs and investigates the choice of the most effective way of protection of the civil rights after discovery of inheritance. The attention has been paid to such way of protection of succession rights as recognition of the legal facts as separate civil legal proceedings. Such legal facts are: ascertainment of the fact of relationship, the family relations, and dependence that give a plaintiff, who is the relative of the dead, the member of his family or the dependent, a possibility to claim inheritance. The article deals with the bases of recognition of the will completely or partly invalid and therefore the legal consequences arising, and also a circle of inheritors who should be disinherited as unworthy ones, as an independent way of protection of succession rights by change of subject structure in the arisen legal relationships. The norm will be valid, if inheritance rights both under the law, and according to the will, will be lost by a person who intentionally committed a crime against life, health, freedom and the dignity of the testator if this circumstance is established by a sentence of court.
Civil Legal Means of Protection of Succession Rights
Keywords: спадкові права; захист спадкових прав; способи захисту спадкових прав; визнання спадкових прав; визнання заповіту недійсним; succession rights; protection of succession rights; ways of protection of succession rights; recognition of succession rights; recognition of the will invalid